Pathogenetic role of the autonomic nervous system in arterial hypotension cardiac remodeling in young women - V. M. Baev; Т. Yu. Agafonova (Кардиоваскулярная терапия и профилактика, 2019)
Aim. To study the features of cardiac remodeling on condition of the autonomic nervous system (ANS) in young women with idiopathic arterial hypotension (IAH).Material and methods. A comparative analysis of the echocardiography data in women with IAH aged 18-25 years with a predominance of sympathetic (n=150) and parasympathetic (n=60) parts of the ANS was performed. The level of systolic blood pressure ≤98 mm Hg worked as the criterion of IAH. The activity of the ANS was evaluated by the I. Kérdö index.Results. It has been shown that women with IAH with sympathicotonia are characterized by a significant decrease in the structural parameters of the heart: the size of all chambers and the aortic ostium, contractile function decrease and a slower relaxation of the left ventricle (LV). Acceleration of intracardiac hemodynamics was observed: an increase in blood flow rates and pressure gradients on the mitral, tricuspid and pulmonary artery valves, an increase in the rates of early and late diastolic LV filling. Changes in early LV diastole are associated with an increase of pressure in the left atrium. We identified a restrictive type of diastolic dysfunction in women with parasympathicotonia.Conclusion. Sympathicotonia and parasympathicotonia in young women with IAH are associated with different heart remodeling variants. Cardiac hypotrophy, decrease of contractile function and impaired LV relaxation during hypotension are associated with low sympathetic activity against the background of parasympathicotonia. The restrictive type of diastolic dysfunction during hypotension is associated with parasympathicotonia. Use of cholinolytics and anticholinesterase reactivators are the potential way of correction of ANS dysfunction, IAH regression and cardiac remodeling.